Microsatellite development for the genus Guibourtia (Fabaceae, Caesalpinioideae) reveals diploid and polyploid species1. (13th July 2016) - Tosso, Felicien; Doucet, Jean‐Louis; Kaymak, Esra; Daïnou, Kasso; Duminil, Jérôme; Hardy, Olivier J.
Abstract : Premise of the study: Nuclear microsatellites (nSSRs) were designed for Guibourtia tessmannii (Fabaceae, Caesalpinioideae), a highly exploited African timber tree, to study population genetic structure and gene flow. Methods and Results: We developed 16 polymorphic nSSRs from a genomic library tested in three populations of G. tessmannii and two populations of G. coleosperma . These nSSRs display three to 14 alleles per locus (mean 8.94) in G. tessmannii . Cross‐amplification tests in nine congeneric species demonstrated that the genus Guibourtia contains diploid and polyploid species. Flow cytometry results combined with nSSR profiles suggest that G. tessmannii is octoploid. Conclusions: nSSRs revealed that African Guibourtia species include both diploid and polyploid species. These markers will provide information on the mating system, patterns of gene flow, and genetic structure of African Guibourtia species.